The role of international environmental law in disaster risk reduction - Peel, Jacqueline, 1974-; Fisher, David (Writer on disaster law) (International environmental law (Martinus Nijhoff), 2016)
In The Role of International Environmental Law in Disaster Risk Reduction, edited by Jacqueline Peel and David Fisher, expert authors from four continents offer perspectives on the growing intersection between environmental law and disaster risk management. Chapters discuss the potential for retasking environmental law tools and principles for purposes of mitigating the harms of potential disasters, including those exacerbated by climate change, and approaches for linking institutions and approaches across the environmental, climate adaptation and disaster risk management fields internationally. This book illustrates the blurring distinction between natural and manmade disasters and the consequences for legal norms and practice in the formerly distinct areas of international environmental law and international disaster law.